(untitled) (Orinoquia, 2020)
Based on prevalence and impact on public health, toxocariasis is an underestimated zoonosis in developing and developed countries. The transmission of Toxocara spp. involves pets, stray dogs and cats (Canis familiaris and Felis catus, respectively), which spread the parasite’s eggs in their feces to the environment. One of the main risk factors for the infection and development of human toxocariasis, is to cohabit with puppies and kittens. For a long time, the preventive strategy for this parasitic infection has been the regular use of antiparasitic drugs to reduce parasite burden in the short term. A long lasting immunological protection can be achieved with vaccination, however, a vaccine is not yet available. Therefore, it is fundamental to know and to understand the state of the art of vaccine development for effective control of this zoonosis. This paper reviews the experimental studies focused on vaccine development for toxocariasis control, and special attention is given to relevant epidemiological studies on the importance of dogs in human toxocariasis.